Development and evaluation of oyster mushroom (Pleurotus ostreatus) incorporated mayonnaise - Greeshma Sree, Mutyala; SINDHU, RITU; Kumari , Anju (Mushroom Research, 2025)
Despite of numerous health benefits, Oyster Mushroom (Pleurotus ostreatus) demand is low, due to shorter shelf life and limited storage technology. This study aimed at development of oyster mushroom incorporated mayonnaise as a value-added product to meet the enhance demand of food industries for convenient as well as a healthier mayonnaise choice. Different gums were used as substitute of egg for the preparation of vegan mayonnaise. Xanthan gum (1% w/v) based variants with 10% oyster mushroom powder was preferred to prepare vegan oyster mushroom mayonnaise and kept under both room temperature and refrigerated temperatures for further studies. Viscosity of mayonnaise samples increased significantly with addition of oyster mushroom powder. During storage, moisture content, pH, emulsion stability, anti-oxidant activity got decreased and titratable acidity, acid value, peroxide value, viscosity of mayonnaise got increased. Addition of preservatives and storage at refrigerated temperature supported the safety and quality of vegan mushroom incorporated mayonnaise.